A comprehensive "Healthy Schools Programme" to promote school health: the Hong Kong experience in joining the efforts of health and education sectors. Issue 3 (1st March 2003) - Lee, A; Tsang, C; Lee, S H; To, C Y
Abstract : Both health and education are linked to economic performance. The success of education depends on good health, and vice versa. Modern education should help young people to determine values, and accept responsibility for their health and social behaviour. The success of health promotion in schools requires the joint efforts of both the health and education sectors. A comprehensive programme is needed to include teachers' training, curriculum development, community participation, changing policies and practices, and research. All these components are needed to build up a successful model of a health promoting school. The "Healthy Schools Programme" in Hong Kong gives a good example of close partnership between the health and education sectors, and moves towards a multidisciplinary approach and active learning towards health promotion.